Iterative estimation method for random interleaver of Turbo codes - Jun LIU; Jing LI; Pei-dong YU (Tongxin xuebao)
Channel coding parameter analysis meant reversely analyzing and estimating the coding parameters,and was one of the key techniques for intelligent communication,information interception and so on.Since Turbo codes were widely used in communication systems,parameter estimation for their interleavers was of great importance.Focusing on the random interleaver of Turbo codes,an iterative estimation algorithm based on correlation decision between the soft outputs of the Turbo decoder was presented.The algorithm used soft-decisions of the demodulator output sequence.It overcame the shortcomings of existing methods which often aimed at certain interleaving structures only,and suffered from weak robustness since they used hard-decisions.Simulation results show that the proposed algorithm has better performance and relatively lower complexity,especially in low signal-to-noise ratio cases.